2016
DOI: 10.1016/j.jagp.2015.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Visual Hallucinations in Eye Disease and Lewy Body Disease

Abstract: Objective: Visual hallucinations (VH) most commonly occur in eye disease (ED), Parkinson's disease (PD), and Lewy body dementia (LBD). The phenomenology of VH is likely to carry important information about the brain areas within the visual system generating them. Methods: Data from five controlled cross-sectional VH studies (164 controls, 135 ED, 156 PD, 79 (PDD 48 + DLB 31) LBD) were combined and analysed. The prevalence, phenomenology, frequency, duration, and contents of VH were compared across diseases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…The majority of patients indicated that their VH began more than 1 year before evaluation and persisted for less than 1 minute, which is consistent with previous research . Also in line with previous studies, the majority of patients with complex VH reported that VH consisted of human figures and animals, whereas patients with simple VH reported seeing flashes, floaters, or movement in the periphery . Similar to Urwyler et al, the majority of the patients indicated that their VH were pleasant, and very few patients experienced frightening or irritating VH.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The majority of patients indicated that their VH began more than 1 year before evaluation and persisted for less than 1 minute, which is consistent with previous research . Also in line with previous studies, the majority of patients with complex VH reported that VH consisted of human figures and animals, whereas patients with simple VH reported seeing flashes, floaters, or movement in the periphery . Similar to Urwyler et al, the majority of the patients indicated that their VH were pleasant, and very few patients experienced frightening or irritating VH.…”
Section: Discussionsupporting
confidence: 88%
“…1 Also in line with previous studies, the majority of patients with complex VH reported that VH consisted of human figures and animals, whereas patients with simple VH reported seeing flashes, floaters, or movement in the periphery. 14,17,32 Similar to Urwyler et al, 14 the majority of the patients indicated that their VH were pleasant, and very few patients experienced frightening or irritating VH. Although complex VH often co-occur with simple VH in PD, 14,16,22,33 in the current study, only 2 participants reported more than 1 type of VH (i.e., simple or complex), whereas 92% reported 1 type of VH.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Visual hallucinations are common in Parkinson disease (PD), 1 particularly as the disease advances, and range from relatively simple flashes of light or color to more complex hallucinations that are typically well-formed images. 2 A number of models 3 , 4 have been proposed to explain the origin of complex recurrent visual hallucinations. Unifying elements across the models include breakdown in communication between cortical regions involved in visual processing, and alteration in the weighting of internal vs external input.…”
mentioning
confidence: 99%
“…dementia VH in dementia tend to be of people/children, animals or objects. 76 Around 50% of patients are significantly distressed by their experiences, with fear and anger being the most common responses. 77 As core defining features of DLB, they are likely to be present at the point of diagnosis, contrasting with AD where VH occur in later stages of cognitive decline, 5 to 6 years after the onset of dementia.…”
Section: Current Practicementioning
confidence: 99%